Intranasal octenidine for methicillin-resistant Staphylococcus aureus (MRSA) carriers and universal octenidine bathing reduced MRSA acquisition in an acute-care general ward. (16th November 2022) - Aung, Aung-Hein; Kyaw, Win Mar; Heng, Yee Kiat; Tey, Hong Liang; Ang, Brenda; Chow, Angela
Abstract: In this quasi-experimental before-and-after study in a methicillin-resistant staphylococcus aureus (MRSA) high-prevalence acute-care dermatology ward from August 2016 to November 2018, patients admitted during intervention period who received additional topical intranasal octenidine were 63% less likely to acquire MRSA than those receiving universal daily octenidine bathing alone during baseline period (aOR, 0.37; 95% CI, 0.14–0.98).